Teleworking in times of COVID-19 - Ramos, Valentina (2020)
One of the impacts that COVID-19 has brought has been social isolation and teleworking. In this sense, telework presents different conditions to traditional ways of working from home, since in these conditions due to the COVI-19, there has been an increase in insecurity, fear and uncertainty. This study analyzes the characteristics of telework and its impact on productivity and well-being in people. The study was carried out in Ecuador, in a sample of 459 people who answered an online questionnaire. The results found demonstrate that there are aspects that affect productivity such as working long hours, personal skills, specifically self-motivation and organizational skills, and mental health. With this research, a better understanding of the situation of teleworking in confinement due to COVID-19 is achieved, allowing both individuals and organizations to develop resources so that work from home is successful and people feel satisfied while this situation lasts. © 2020, Sociedad Interamericana de Psicologia. All rights reserved.